Frequent Recurrences of Genital Herpes Are Associated with Enhanced Systemic HSV-Specific T Cell Response - Michal Holub; Alžběta Stráníková; Pavel Chalupa; Simona Arientová; Kateřina Roubalová; Ondřej Beran (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objectives. Genital herpes simplex virus (HSV) infection is controlled by HSV-specific T cells in the genital tract, and the role of systemic T cell responses is not fully understood. Thus, we analysed T cell responses in patients with recurrent genital herpes (GH). Methods. T cell responses to HSV-1 and HSV-2 native antigens and the expression of HLA-DR and CD38 molecules on circulating CD8+ T cells were analysed in adults with high frequency of GH recurrences (19 patients) and low frequency of GH recurrences (7 patients) and 12 HSV-2 seronegative healthy controls. The study utilized the interferon-γ Elispot assay for measurement of spot-forming cells (SFC) after ex vivo stimulation with HSV antigens and flow cytometry for analysis of the expression of activation markers in unstimulated T cells. Results. The patients with high frequency of GH recurrences (mean number of recurrences of 13.3 per year) had significantly enhanced HSV-specific T cell responses than the HSV-2 seronegative healthy controls. Moreover, a trend of higher numbers of SFC was observed in these patients when compared with those with low frequency of GH recurrences (mean number of recurrences of 3.3 per year). Additionally, no differences in CD38 and HLA-DR expression on circulating CD8+ T cells were found among the study groups. Conclusions. Frequency of GH recurrences positively correlates with high numbers of systemic HSV-specific T cells.